In silico analysis of gene expression in V3a and the superior occipital gyrus: Relevance for migraine. (16th October 2020) - Lisicki, Marco; Carpinella, Mariela; Coppola, Gianluca; Zamparella, Tatiana Castro; Ruiz-Romagnoli, Emiliano; Manise, Maïté; de Noordhout, Alain Maertens; Schoenen, Jean; Magris, Diego Conci
Introduction: Visual manifestations are the most prominent non-painful features of migraine. During the last decades, visual area V3a has gathered attention of headache scientists because of its apparent implication on aura initiation, photophobia and cortical hyper-responsiveness related to visual motion perception. In this hypothesis-generating study, we performed an in silico analysis of gene expression in left V3a and the cerebral gyrus that harbours it (left superior occipital gyrus (lSOG)) searching for transcriptomic patterns that could be linked with migraine's pathophysiology. Materials and methods: Neurotransmitter receptor gene expression levels in left V3a were extracted from validated brain mRNA expression models using a probabilistic volumetric mask of this region. The primary visual cortex and other sensory cortices (auditory, olfactory and somatosensory) were used as comparators. Genome-wide transcriptomic differences between the gyrus harbouring left V3a (lSOG) and the rest of the cerebral cortex were assessed using the Allen Brain Institute Human RNA micro array atlas/database. Results: Adrenergic receptor β1, dopaminergic receptor D3 and serotoninergic receptors 1B, 1F and 2A, which have been previously implicated in migraine's pathophysiology and/or treatment, showed significantly higher expression levels on left V3a. Transcriptomic differences between the lSOG harbouring V3a and the rest of the cortex comprise genes whose products are involved in neuronal excitability (SLC17A6, KCNS1, KCNG1 and GABRQ), activation of multiple signal transduction pathways (MET) and cell metabolism (SPHKAP via its interaction with cAMP-dependent protein kinase). Conclusions: Focal gene expression analysis of V3a suggests some clues about its implication in migraine. Further studies are warranted.